2016
DOI: 10.3174/ajnr.a5028
|View full text |Cite
|
Sign up to set email alerts
|

Differential Interstrain Susceptibility to Vertebrobasilar Dolichoectasia in a Mouse Model

Abstract: C57BL/6J mice demonstrated greater susceptibility to vertebrobasilar dolichoectasia induction than SV129 mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 17 publications
(21 reference statements)
0
18
0
Order By: Relevance
“…C57BL/6J mice had a greater susceptibility to VBD induction than SV129 mice. 71 These findings are important for identifying pivotal elements relevant to the development of VBD. In the future, linkage analysis of different strains may provide new insight into the genetic determinants of VBD susceptibility.…”
Section: Genetic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…C57BL/6J mice had a greater susceptibility to VBD induction than SV129 mice. 71 These findings are important for identifying pivotal elements relevant to the development of VBD. In the future, linkage analysis of different strains may provide new insight into the genetic determinants of VBD susceptibility.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…In the C57BL/6J mice, the researchers demonstrated arterial wall dilation and elongation characterized by internal elastic lamina disruption, muscular layer discontinuity, inflammatory cell infiltration, and high MMP expression in the media. C57BL/6J mice had a greater susceptibility to VBD induction than SV129 mice [ 71 ]. These findings are important for identifying pivotal elements relevant to the development of VBD.…”
Section: Mechanisms Underlying the Association Between Iade And Csvdmentioning
confidence: 99%
“…A prospective study demonstrated that MMP-2 played a role in the etiology of dolichoectasia of cervical and intracranial carotid arteries (11). A mouse model study showed that dolichoectasia was associated with high levels of MMP-2 and MMP-9 (12). A clinical study demonstrated that dolichoectasia was associated with lower plasma levels of MMP-3 (13).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, VBD has been reported to be associated with elevated levels of MMP-9 expression alone or combined with low levels of TIMP-2 expression among individuals with HIV infection (Gutierrez et al, 2016). In a study using a mouse model focusing on differential inter-strain susceptibility to VBD, dolichoectasia was also reported to be associated with high MMP-12 and MMP-9 (Zhu et al, 2017). On the contrary, in a prospective cohort study of stroke patients, dolichoectasia was reported to be connected to a lower plasma level of MMP-3 (Pico et al, 2010).…”
Section: Introductionmentioning
confidence: 99%